A revision of Sphaeridops (Hemiptera: Heteroptera: Reduviidae) - Gil-Santana, Hélcio R. (Zootaxa, 2021)
Based on a re-examination of the type materials of all described species and additional non-type specimens, the genus Sphaeridops Amyot & Serville, 1843 (Hemiptera: Heteroptera: Reduviidae: Sphaeridopinae) is revised. Sphaeridops eulus Maldonado & Santiago-Blay, 1992 is downgraded to a new synonym of S. amoenus (Lepeletier & Serville, 1825); S. pallescens (Walker, 1873), erroneously treated as a junior synonym of S. amoenus by previous authors, is revalidated. A revised diagnosis and a redescription of the genus and its included species are given, all species are illustrated, and an updated key to the species of Sphaeridops is presented.